Gereja dan Ritual Tolak Bala dalam Masyarakat Dayak - Wokal, Valens Viktori Bain; Rovensius, Domesius; Kwirinus, Dismas (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2020)
The article argues that tolak bala, the name ofan important ritual for the Dayak people,is intended to dispel any negative power out of the people and to guarantee the well-being of the community. It is performed every time the people experience the destructive effects of an unidentifed power that make people sick even cause death. Formerly, tolak bala was performed quite regularly. Since the covid-19 has become pandemic worldwide, the traditional ritual of tolak bala has also attracted the concern of the people. The writers try to deal with this new phenomenon based on their Christian faith. They then suggest that the Church should take the tolak bala ritual quite seriously and promote an intense dialogue with Christian faith in such a way that the people would not be dissociated from the True God as the Lord Jesus has taught his disciples.